In silico studi of Orthosiphon aristatus as antioxidant - Dian Novita; Imam Agus Faizal (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2020)
Orthosiphon aristatus (O. aristatus) is a herbal plant that has antioxidant activity. This study was conducted in a preliminary study of the potential active compound O. aristatus with in silico software pyrex autodock vina method, and visualization using biovia discovery studio. Results from the study in silico showed that O.aristatus extract has potential as an antioxidant compound. Result value of binding affinity with SOD receptor proteins having more negative values compared to control compounds. The interaction of O.aristatus extract is quite potential as an antioxidant, through hydrogen bonding that is equal to control, namely vitamin E